Organik Matter: It’s Role in Sustainable Farming of Sugarcane - Djajadi Djajadi (Puslitbang Perkebunan, 2015)
ABSTRACTOrganik matter has an important role in determining soil health of sugarcane, i.e. soil capacity to support sugarcane to produce sustainable high yield. Soil organic matter influences soil physical, chemical, and biological properties, so that a consequence of declining soil organic matter is poorer soil fertility and lower yield. This paper has an objective to elucidate the important role of organic matter on sustainable farming of sugarcane. The important role of organic matter in soil fertility has been known for a long time before Green Revolution concept was introduced. With more intensity in sugarcane farming and more increasing of sugar demand, application of organic fertilizer started to be substituted by chemical fertilizer. Using green manure and/or biofertilizer has a chance to be spread out to the farmers due to more practical and more efficient than solid organik fertilizer, such as dung manure or compost. Future research should be focusing on the efectivity of green manure and or biofertilzer sources in improving soil fertility and cane yield, minimizing soil pathogen, reducing soil erosion of sugar cane land monoculture, and improving awareness of farmers about soil degradation as consequences of sugarcane monoculture planting for years.Keywords: Organic matter, sugarcane, soil health sustainable farming Bahan Organik: Peranannya dalam Budidaya Tebu BerkelanjutanABSTRAKBahan organik tanah berperan penting dalam menentukan kesehatan tanah tebu, yaitu kapasitas tanah yang dapat mendukung produksi tebu yang tinggi secara berkelanjutan. Kadar bahan organik tanah mempengaruhi sifat fisik, kimia dan biologi tanah. Paper ini bertujuan untuk menguraikan tentang peranan bahan organik dalam memperbaiki sifat fisik, kimia dan biologi tanah pertanaman tebu. Pentingnya peran bahan oganik tersebut sudah disadari dari dulu, sehingga sebelum revolusi hijau penggunaan pupuk organik sudah umum dilakukan petani. Dengan semakin intensifnya budidaya tebu dan semakin meningkatnya kebutuhan gula, pemanfaatan pupuk organik sudah jarang dilakukan. Diperlukan usaha untuk meningkatkan dan mempertahankan kadar bahan organik pada lahan tebu, antara lain berupa gerakan masal dalam bentuk gerakan nasional melalui program aplikasi bahan organik. Pemanfaatan pupuk hijau dan/atau pupuk hayati berpeluang untuk diterapkan karena lebih praktis dan efisien daripada penambahan pupuk organik padat. Penelitian ke depan perlu difokuskan untuk mengkaji jenis-jenis pupuk organik dan pupuk hayati yang efektif memperbaiki kesuburan, dalam menekan serangan penyakit, meminimalkan erosi pada lahan-lahan tebu monokultur, dan meningkatkan kesadaran petani tebu tentang terjadinya degradasi lahan akibat penanaman tebu yang terus menerus.Kata kunci: Bahan organik, tebu, kesehatan tanah, budidaya berkelanjutan